Comparative performance of distinct frailty measures among patients undergoing percutaneous left atrial appendage closure. Issue 3 (10th January 2023) - Wang, Allen; Ferro, Enrico G; Xu, Jiaman; Song, Yang; Sun, Tianyu; Strom, Jordan B; Kim, Dae H; Yeh, Robert W.; Ko, Darae; Kramer, Daniel B
Abstract: Aims: Frailty is associated with increased morbidity and mortality in patients undergoing left atrial appendage closure (LAAC). This study aimed to compare the performance of two claims‐based frailty measures in predicting adverse outcomes following LAAC. Methods: We identified patients 66 years and older who underwent LAAC between October 1, 2016, and December 31, 2019, in Medicare fee‐for‐service claims. Frailty was assessed using the previously validated Hospital Frailty Risk Score (HFRS) and Kim Claims‐based Frailty Index (CFI). Patients were identified as frail based on HFRS ≥5 and CFI ≥0.25. Results: Of the 21, 787 patients who underwent LAAC, frailty was identified in 45.6% by HFRS and 15.4% by CFI. There was modest agreement between the two frailty measures (kappa 0.25, Pearson's correlation 0.62). After adjusting for age, sex, and comorbidities, frailty was associated with higher risk of 30‐day mortality, 1‐year mortality, 30‐day readmission, long hospital stay, and reduced days at home ( p  < .01 for all) regardless of the frailty measure used. The addition of frailty to standard comorbidities significantly improved model performance to predict 1‐year mortality, long hospital stay, and reduced days at home (Delong p ‐value < .001). Conclusion: Despite significant variation in frailty detection and modest agreement between the two frailty measures, frailty status remained highly predictive of mortality, readmissions, long hospital stay, and reduced days at home among patients undergoing LAAC. Measuring frailty in clinical practice, regardless of the method used, may provide prognostic information useful for patients being considered for LAAC, and may inform shared decision‐making in this population.